Analisis Kinerja Sistem Proteksi Berdasarkan Peramalan Beban Pada Penyulang Galunggung - Mochammad , Mieftah; Bakti Indra Kurniawan; Ridzki , Imron; Sutjipto, Rachmat (Elposys: Jurnal Sistem Kelistrikan, 2023)
The Galunggung feeder has a total line length of 10.68 kilometers and is supplied by power transformer number 1 at the Polehan substation, with a capacity of 30 MVA. As of December 2020, the peak load on the Galunggung feeder was recorded at 231.4 A, while the lowest load was 133.9 A. Up to the current condition, the Galunggung feeder is operating within standard parameters, with a voltage drop of 0.434 kV or 2.17%. However, it is possible that with future developments and an increase in the number of customers over the years, the energy demand will also increase. Due to this additional energy demand, the protection system may require adjustments to accommodate the increased load.After conducting load forecasting using simple linear regression, a forecast for the next 10 years was obtained. In the year 2030, it is anticipated that the Galunggung feeder will experience a 24% increase in load. With this load increase and no changes to transformers or conductors, there will be no alterations to impedance and short-circuit current calculations. Therefore, no protection setting adjustments are necessary. The recommended action would be to upgrade some transformers that are approaching their capacity limits.